1998
DOI: 10.1002/(sici)1097-4547(19980815)53:4<415::aid-jnr3>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Microglial cells prevent nitric oxide-induced neuronal apoptosis in vitro

Abstract: Apoptotic neuronal death is known to occur in the developing brain and in the mature brain of patients with ischemic and degenerative disorders. Although microglial cells are known to become activated in specific conditions, it has not been elucidated whether they enhance or prevent neuronal apoptosis. The present study was intended to observe how microglial cells are involved in neuronal death. When rat primary cortical neurons were incubated with a nitric oxide (NO) donor sodium nitroprusside (SNP; 300 micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(57 citation statements)
references
References 31 publications
2
54
1
Order By: Relevance
“…67 Patients with severe type I plasminogen deficiency (plasminogen activity and antigen both extremely low) exhibit the neurologic developmental defect of symmetric internal hydrocephalus with a Dandy-Walker malformation, hypoplasia of the cerebellum, and a hypoplastic corpus callosum. 68 Because development of neurologic pathways requires apoptosis, the presence of this defect is consistent with defective apoptosis in these patients and mice.…”
Section: Discussionmentioning
confidence: 99%
“…67 Patients with severe type I plasminogen deficiency (plasminogen activity and antigen both extremely low) exhibit the neurologic developmental defect of symmetric internal hydrocephalus with a Dandy-Walker malformation, hypoplasia of the cerebellum, and a hypoplastic corpus callosum. 68 Because development of neurologic pathways requires apoptosis, the presence of this defect is consistent with defective apoptosis in these patients and mice.…”
Section: Discussionmentioning
confidence: 99%
“…Neuronal cells isolated from the hippocampus or cerebellar cortex were cultured as described above in the absence or presence of natural murine nerve growth factor (NGF) (Life Technologies, Inc.), recombinant human brain-derived neurotrophic factor (BDNF; PeproTech, Inc.), recombinant human transforming growth factor ␤1 (TGF-␤1; PeproTech, Inc.), and recombinant murine tumor necrosis factor alpha (TNF-␣; PeproTech, Inc.). To estimate the cell survival, Alamar blue fluorescent dye (Alamar Biosciences, Sacramento, Calif.), which is a redox indicator to assess viability and mitochondrial activity of the cells (40,41), was used by following a protocol manual for Fluoroskan Ascent (Labsystems). The culture method that we used induces the differentiation of neurons, during which mitochondrial numbers and activity in the individual neuronal cells increase.…”
Section: Methodsmentioning
confidence: 99%
“…In this context, we demonstrated that STAM1 Ϫ/Ϫ primary hippocampal neurons were more sensitive to death induced by kainic acid and an NO donor in vitro than were wild-type neurons. Since both kainic acid (3,29) and NO donors (29,36,37) are known to induce neuronal cell death, it can be assumed that STAM1 may have a role in protection against these stresses in hippocampal neurons. The NO donor-induced neuronal apoptosis could be inhibited by antiapoptotic proteins, such as Bcl-2 and Bcl-X (36); however, when we investigated the expression of Bcl-2 and Bcl-X in STAM1…”
Section: Discussionmentioning
confidence: 99%
“…The cultured neurons were resuspended in Neurobasal medium plus B27 supplement but minus AO (Life Technologies) supplement, because B27 supplement contains some antioxidants. They were exposed to 150 M kainic acid or 50 M sodium nitroprusside (SNP) for 24 h and stained for 2 h with 10% Alamar blue dye (Alamar Biosciences, Sacramento, Calif.), which is a redox indicator, to assess the viability and metabolic activity of the cells (37,42). The light absorbance of the reduced form of the dye was measured at 540 nm, whereas the oxidized form was measured at 620 nm.…”
Section: Methodsmentioning
confidence: 99%